Improving Retention of Healthcare Workers At Service Industry Through to Compensation Strategies - Maratu Solihah; Ratna Indrawati; Hasyim Hasyim (Penerbit Kemala Indonesia, 2021)
Low retention of healthcare workers may have a negative impact on the service industry's performance and effectiveness. There are several major factors which caused to low retention of healthcare workers including, compensation provided by industry that does not meet employee expectations, and there is no stipulated compensation for overtime work in the form of incentives or bonuses. In addition, the organizational commitment to the healthcare workers is still considered low, due to the service industry’s operations which have only been running for one year. This study intended to provide empirical evidence of the impact of compensation and motivation on retention of healthcare workers mediated by organizational commitment. The quantitative methods with the type of causality study are used in this study. The data for this study were obtained from the primary data. All healthcare employees with a service time of more than one year were included in the individual analysis. Path analysis was used to analyse the data obtained in this study. The results of the study indicated that compensation, motivation and organizational commitment simultaneously had a positive and significant effect on the retention of healthcare workers with organizational commitment as an intervening variable. Furthermore, compensation and motivation partially had a positive and significant effect on organizational commitment. Moreover, compensation, motivation and organizational commitment contributed to a positive and significant effect on the retention of healthcare workers. Findings of the study indicated that the direct effect of compensation and motivation on the retention of healthcare workers was greater than that mediated by organizational commitment.